Research on mechanical properties and prediction methods of hybrid fiber concrete for airport pavements - Wenyuan Xu; Zhen Zang; Xiu Liu; Yongcheng Ji; Jianbo Xu; Hao Li (PLoS ONE, 2025)
The cement concrete pavement at airports is prone to fatigue cracking due to dynamic loads from airplanes and environmental coupling effects. This research developed a strength prediction model and introduced a novel hybrid fiber effect coefficient (RH) by conducting both single and mixed experiments with polypropylene (PP), polyvinyl alcohol (PVA), basalt (BF), and polyacrylonitrile (PAN) fibers, alongside mechanical testing and significance analysis. All three hybrid fibers exhibited favorable hybrid effects, with optimal dosages as follows: compressive strength for PPFRC (0.38, 0.11), BFRC (0.6, 0.4), PNCC (0.5, 0.1); and flexural strength for PPFRC (0.5, 0.1), BFRC (0.6, 0.03), PNCC (0.4, 0.1), respectively. This accomplishment can be utilized in future airport engineering, offering distinct alternatives for runways (ideally BFRC) and aprons (preferably PPFRC/PNCC), substantially prolonging road surface lifespan to 20 years and diminishing comprehensive maintenance expenses.